2018
DOI: 10.1186/s12885-018-4301-1
|View full text |Cite
|
Sign up to set email alerts
|

The alterations of cytokeratin and vimentin protein expressions in primary esophageal spindle cell carcinoma

Abstract: BackgroundThe accumulated evidence has indicated the diagnostic role of cytokeratin (CK) and vimentin protein immunoassay in primary esophageal spindle cell carcinoma (PESC), which is a rare malignant tumor with epithelial and spindle components. However, it is largely unknown for the expression of CK and vimentin in pathological changes and prognosis of PESC.MethodsEighty-two PESC patients were identified from the esophageal and gastric cardia cancer database established by Henan Key Laboratory for Esophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Immunohistochemistry showed the squamous cells stained positively for cytokeratin and the stromal cells for vimentin. These findings are consistent with the general features of esophageal pseudosarcoma, which is a rare subtype of spindle cell carcinoma (SpCC) [1]. SpCC is characteristically a polypoid mass with intermingled spindle cell and squamous cell components [2].…”
supporting
confidence: 85%
“…Immunohistochemistry showed the squamous cells stained positively for cytokeratin and the stromal cells for vimentin. These findings are consistent with the general features of esophageal pseudosarcoma, which is a rare subtype of spindle cell carcinoma (SpCC) [1]. SpCC is characteristically a polypoid mass with intermingled spindle cell and squamous cell components [2].…”
supporting
confidence: 85%
“…SCC often shows positivity for vimentin and p53 on immunohistochemistry, whereas the epithelial component is frequently positive for pan cytokeratin (AE1/AE3). Li et al [ 8 ] reported that, in 23.2% of cases of primary esophageal SCC, both the spindle cells and the epithelial cells were positive for AE1/AE3, and in 8.5% of cases, both components were also positive for vimentin. In the present case, AE1/AE3 expression was limited to only a small portion, with loss of epithelial characteristics in the majority, suggesting difficulty in making a definitive diagnosis on biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomatous spindle cells demonstrated very weak immunoreactivity of epithelial markers in our present case. However, Li et al (2018) reported that AE1/AE3 were positive in sarcomatous components in only 23% of cases. Therefore, the absences of immunoreactivity of epithelial markers in sarcomatous components could not exclude the possibility of a concept of monoclonal origin.…”
Section: Discussionmentioning
confidence: 99%